2019
DOI: 10.21037/jtd.2019.08.42
|View full text |Cite
|
Sign up to set email alerts
|

Poor enhancement pattern of left atrial appendage in cardiac computed tomography is associated with stroke in persistent atrial fibrillation patients

Abstract: Background: In atrial fibrillation (AF) patients, the left atrial appendage (LAA) is the major source of thrombi. We assessed the hypothesis that poor contrast enhancement in the LAA during the early phase of cardiac computed tomography (CT) predicts a high risk of thrombus formation, leading to cardiogenic stroke. Methods: We studied 147 consecutive patients with chronic AF who underwent cardiac CT. Three different patterns of medium contrast enhancement in the LAA were used to categorize the stroke risk: poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In addition to the above qualitative methods, there are some quantitative methods such as calculating the LAA/ascending aorta (AA), the Hounsfield unit ratio, controlling the delay time of delayed scanning, and assessing the enhancement pattern based on dual-phase CT [17,29,30]. It is worth mentioning that, referring to the LAA/AA ratio, Chun et al [17] confirmed that single-phase, CTA-based radiomics was superior to the early LAA/AA ratios and similar to the delayed LAA/AA ratios for identifying LAAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above qualitative methods, there are some quantitative methods such as calculating the LAA/ascending aorta (AA), the Hounsfield unit ratio, controlling the delay time of delayed scanning, and assessing the enhancement pattern based on dual-phase CT [17,29,30]. It is worth mentioning that, referring to the LAA/AA ratio, Chun et al [17] confirmed that single-phase, CTA-based radiomics was superior to the early LAA/AA ratios and similar to the delayed LAA/AA ratios for identifying LAAT.…”
Section: Discussionmentioning
confidence: 99%
“…The scanning range was from pulmonary trunk to the bottom of heart. Al were injected with a total of about 50 mL of non-ionic iodinated contrast medium I/mL) via the right median cubital vein at a flow rate of 5.0 mL/s via a power in lowed by 30…”
Section: Ct Image Acquisition and Analysismentioning
confidence: 99%